Evaluation and optimization of efficiency of power plants / Amirhoushang Zaferanlo - Amirhoushang, Zaferanlo (2018)
Power generation is one of most vital topics currently; therefore there have been a lot of studies on this topic ranging from fossil energy sources to solar and nuclear energies. However high demand on fossil fuels need to come to a stop due to all the destructive effects. The amount of energy loss in power plants which use fossil fuels is quite high. Hence most of these studies also include new methods to minimize these energy losses as much as possible. In this research, studies have been conducted in order to improve the efficiency of Kish gas power plant which is located in Iran. The primary objectives of this study are analyzing the system component separate1y and based on the understanding achieved, methods is suggested to avoid energy losses as well as producing more output work. Performance of the plant was estimated by component-wise modeling and a detail break-up of the inlet and output of each part of power plant components. As per the analysis, the power output of Kish power plant which has seven turbines is 25 MW without losses through condenser. Two boilers and a condenser have the major role in the power output and according to analysis boiler and condenser are main part of this study in order to see the effect of pressure and temperature on Rankin cycle which is the main modelling used to achieve the objectives.